2014
DOI: 10.5539/gjhs.v6n6p154
|View full text |Cite
|
Sign up to set email alerts
|

Recovery Based on Spirituality in Substance Abusers in Iran

Abstract: Background and Purpose:Spirituality is an important factor influencing the decrease of substance abuse severity and maintenance of the recovery phase. This research, investigates the effect of spiritual experiences in the recovery of substance abusers.Material and Methods:Qualitative data was collected from 16 men and 6 women, selected through purposeful sampling to ensure an equilibrated gender representation and data from different recovery periods. Data were collected via semi-structured interviews.Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 21 publications
1
15
0
5
Order By: Relevance
“…These results are also in line with the results of Chang (2017) (29). In this regard, Stensma (2005) also argues that drug users should be mentally engaged with their problems to figure out their negative conditions and try to escape from it (30). Doing so, women drug users can gain selfconfidence and knowledge, and come to a deep understanding of their conditions to get on their way back to life.…”
Section: Discussionsupporting
confidence: 64%
“…These results are also in line with the results of Chang (2017) (29). In this regard, Stensma (2005) also argues that drug users should be mentally engaged with their problems to figure out their negative conditions and try to escape from it (30). Doing so, women drug users can gain selfconfidence and knowledge, and come to a deep understanding of their conditions to get on their way back to life.…”
Section: Discussionsupporting
confidence: 64%
“…Another finding is that, at the pinnacle of helplessness, believing in God's mercy and resorting to spirituality was a way to return from addiction to life. Research has confirmed the positive role of spirituality at the start of the rehabilitation process and reducing the likelihood of relapse to drug use [31]. In a study, the findings showed the positive results in those who paid attention to proper nutrition, exercise and spirituality in their rehabilitation process [32].…”
Section: Discussionmentioning
confidence: 98%
“…The data infers it is through prayers that the family pleads and thanks the Superior Being for the recovery of the drug dependent. Studies show that prayer constitute a therapeutic instrument or resource [15][16][17] both to the ill relative and to the family, as it promotes tranquility, inner peace, minimizes suffering, provide confort 18 and hope in the recovery. 14 The relatives taking part in this study recognized that the religious environment facilitate the access to messages of Christian content, transmitted through its representatives, which Family strengths and the chemical dependence Claus MIS, Zerbetto SR, Gonçalves AMS, Galon T, Andrade LGZ, Oliveira FC provide strength, tranquility and teachings.…”
Section: Discussionmentioning
confidence: 99%